1992
DOI: 10.1557/proc-258-505
|View full text |Cite
|
Sign up to set email alerts
|

Defect Kinetics and Saturation in Amorphous Silicon-Germanium Alloys

Abstract: A quantitative comparison of defect kinetics under high-intensity light-soaking was carried out on a-Si:H and a-SiGe:H. A simple technique that ensures identical experimental conditions (generation rates and generation profiles) in samples of different bandgaps is demonstrated. It is shown that the apparent dependence on bandgap of the susceptibility to light-induced degradation is mainly due to changes in intrinsic carrier concentrations without the need to adhere to any structural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
3
2
Order By: Relevance
“…An important difference between these two figures is that the slope of [ls soak / ls anneal ] -1 is approximately two times higher than that of [a (1.0 eV) soak /a (1.0 eV) anneal ], indicating that defects causing the degradation of gls-products and increase of sub-bandgap absorption coefficient, a (1.0 eV), are not the same type of defects. Insignificant degradation kinetics of high Ge concentration alloys were also reported in previous investigations [10,15,36]. These results indicate that degradation kinetics in a-Si:H and a-SiGe:H alloys with Ge concentration up to 28% are similar in nature as in agreement with previous reports.…”
Section: Light Soaked Statesupporting
confidence: 92%
See 2 more Smart Citations
“…An important difference between these two figures is that the slope of [ls soak / ls anneal ] -1 is approximately two times higher than that of [a (1.0 eV) soak /a (1.0 eV) anneal ], indicating that defects causing the degradation of gls-products and increase of sub-bandgap absorption coefficient, a (1.0 eV), are not the same type of defects. Insignificant degradation kinetics of high Ge concentration alloys were also reported in previous investigations [10,15,36]. These results indicate that degradation kinetics in a-Si:H and a-SiGe:H alloys with Ge concentration up to 28% are similar in nature as in agreement with previous reports.…”
Section: Light Soaked Statesupporting
confidence: 92%
“…Contrarily, the density of deep defects in the bandgap increases with increased Ge alloying which finally degrades the lifetime of photogenerated carriers [3][4][5]. Even though earlier studies reported negligible Staebler-Wronski effect (SWE) in a-SiGe:H mainly due to poor material quality available at those times [6,7], high quality alloy films prepared after improved deposition systems exhibited a substantial SWE under light soaking similar to that intrinsic to pure a-Si:H [8][9][10][11][12][13][14][15][16]. For this reason, investigations of the light induced defect creation as well as native defects in the alloy as a function of Ge content has become an important issue to be understood and resolved both scientifically and technologically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion would not be changed even if LS was performed under identical generation rates, and it is in agreement with previous works reporting that the rate for light-induced defect creation decreases with the band-gap narrowing. 31 We find very low values of for the low Ge content samples (xр0.15), of the order of a few seconds only, which are lower than usually found in the literature. 31,32 We finally note that our LS duration of 10 5 s was not sufficient to reach the fully saturated light-degraded photocurrent value for high Ge content samples ͑xϭ0.32 and 0.35͒.…”
Section: Light Soakingcontrasting
confidence: 55%
“…However, increasing the Ge content of the alloy creates higher density of deep defects in the bandgap, which finally degrades the lifetime of photo generated carriers [3][4][5][6]. First investigations on the light induced degradation reported negligible Staebler-Wronski effect (SWE) [7,8], however, high quality alloy films prepared after improved deposition systems exhibited a substantial SWE under light soaking [9][10][11][12][13]. For this reason, investigations of the light induced defect creation as well as native defects in the alloy as a function of Ge content has become an important issue to be understood both scientifically and technologically.…”
mentioning
confidence: 99%